Sustainable agriculture research and education - a model for cooperation and collaboration - Ebert, Kerri (Kansas State University, 2011)
Funded by the United States Department of Agriculture National Institute for Food and Agriculture since 1988, the SARE program is a participatory and inclusive system that supports and promotes sustainable farming and ranching. SARE offers competitive grants and educational opportunities for producers, scientists, educators, institutions, organizations, and others exploring sustainable agriculture. The SARE mission is to provide grantmaking and outreach to advance sustainable innovations to the whole of American agriculture. Through its outreach activities SARE provides field-ready, field-tested information in print and electronic formats. The SARE model takes a holistic approach to research and education. Agricultural producers, university researchers, non-governmental agencies, and Extension educators are included at all levels of program administration. SARE provides competitive grant opportunities for formal university-based research and education; farmer/rancher/producer research; on-farm partnership studies; graduate student research; and youth/youth educator programming. In addition, each state receives funding for professional development activities to facilitate transfer of current sustainable agriculture research and practices to professionals who work directly with farmers, such as Extension educators and USDA employees.
Keywords: Sustainability; Agriculture